Impact of polycystic ovary syndrome on the atherogenic plasma index: A retrospective analysis - Huseyin Demirci; Burak Menekse; Enes Ucgul; Yuksel Onaran; Seyit Murat Bayram; Erman Cakal (BMC Endocrine Disorders)
Abstract Background Polycystic ovary syndrome (PCOS) is the most common metabolic disorder in women and is characterized by chronic oligomenorrhea and hyperandrogenism, often accompanied by insulin resistance. In women with PCOS, insulin resistance, hyperandrogenism, and impaired lipid metabolism contribute to an increased risk of atherogenesis. Methods Our study was conducted retrospectively on 347 women with PCOS and 132 healthy women who presented at our clinic. The impact of PCOS on the atherogenic plasma index (AIP) was assessed using multivariable linear regression analysis. Results The AIP was significantly greater in women with PCOS than in controls (p-value < 0.001). A marked increase in AIP was observed when the body mass index (BMI) was ≥ 35 kg/m² (p-value < 0.001). AIP was positively correlated with BMI (r = 0.174, p-value = 0.001) and the homeostatic model assessment for insulin resistance (HOMA-IR) score (r = 0.294, p-value < 0.001). In the multivariable linear regression model including all participants, PCOS diagnosis (B = 0.146, 95% CI = 0.082–0.210; p-value < 0.001) and HOMA-IR (B = 0.017, 95% CI = 0.011–0.022; p-value < 0.001) independently predicted higher AIP. These findings identify PCOS and insulin resistance as independent risk factors for increased atherogenicity. Conclusions PCOS diagnosis and HOMA-IR are independent risk factors for increased atherogenicity. The increased atherogenic burden in women with PCOS can be assessed by the AIP. A significant increase in atherogenicity was observed in patients with a BMI of 35 kg/m² or higher.